EFFICACY OF AEROBIC EXERCISE IN THE TREATMENT OF MECHANICAL SHOULDER, LUMBAR AND KNEE PAIN - SM Smailnejad Ganji, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Mechanical shoulder, lumbar and knee pain is common on musculoskeletal system. Anti-inflammatory agents and physiotherapy are used for treatment of these conditions and unfortunately are unsuccessful. The purpose of this study was to assess the efficacy of aerobic exercise in the treatment of mechanical shoulder, lumbar and knee pain.METHODS: This semi- experimental study was conducted on 450 patients suffering from mechanical shoulder pain (150 patients), mechanical lumbar pain (150 patients) and mechanical knee pain (150 patients) referred to the clinic of orthopedics, Babol medical University from 2004 to 2006. All of these cases were educated to pain reduction or painless conditioning. Subjects were advised to do aerobic exercises such as swimming, running, walking and bicycling for one hour per day. They were followed at 2 month interval for 18 months. Cure rate in these three groups were compared.FINDINGS: The mean age of cases with shoulder, lumbar and knee pain was 36±22, 41±28 and 48±25 years, respectively. Duration of pain was 83±45, 93±80 and 48±30 days, respectively. Complete resolution of pain was seen in 80% of patients in shoulder group and in 88% of lumbar group and in 73.3% of knee group. Cure rate was significantly higher in patients suffered from spinal pain than to the other groups (p=0.03).CONCLUSION: The results showed that aerobic exercise is effective for treatment of mechanical pain. So establishing exercise program especially aerobic exercise should be considered as a way to prevent common musculoskeletal pains in community.